5G Quality of Service (QoS) - Mechikel Elhocine; Abidi Salah Eddine; Ramdani Saadi (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2021)
The fifth-generation mobile network that will replace the fourth-generation cellular technology with multiple super data speeds up to 10 gigabits per second, a very low arrival time of less than milliseconds. It also promises to accelerate the development and widespread adoption of many emerging innovations, which are currently limited to smart cities and selfdriving vehicles. On the peripheral public awareness, like the Internet of Things in this work, we did a study on the quality of service in the fifth generation, which plays an important role in this technology and which will provide several advantages in terms of speed and low loss of data that were a problem in previous generations. We will use Matlab to simulate one of the techniques that will improve the quality of service and avoid the loss of packages, where we simulated the multi-antenna technology that has proved effective.
OPTION: Telecommunication Systems